Taxonomical status of Andreaea clavata var. tenuior Broth. (Bryophyta, Andreaeaceae) - Suárez, Guillermo M. (Phytotaxa, 2024)
The moss genus Andreaea Hedwig (1801:47) (Andreaeaceae Dumort., Bryophytina Engl.) is found growing on acid and neutral rocks in cool temperate to subpolar environments, as well as in the high altitude mountains of tropical and subtropical regions (Murray 1988). The genus include between 15 and 20 species in the Andean region (Churchill et al. 2020) with many taxa still poorly known. Andreaea clavata Broth. (in Herzog 1916:10) is only know from two collections, one from Bolivia and one from Peru (Hermann 1976; Menzel 1992).